The Discovery of Ultrasound Irradiation as a Useful Tool for Accelerating Petasis Three-component Reaction: Synthesis of α-Arylglycines - Yun, Fan; Cheng, Chunhui; Li, Jingxuan; Tang, Pingwah; Yuan, Qipeng (Current Organic Synthesis, 2018)
Aim and Objective: α-Arylglycines belong to an important class of non-proteinogenic amino acids. Petasis 3-component, one-pot reaction lends itself to be suitable for the synthesis of α-Arylglycines. Because of the low reactivity, Petasis reaction requires long reaction time. Our objective is to use ultrasound irradiation to accelerate this versatile Petasis' synthesis of α-Arylglycines. Materials and Methods: Ultrasound irradiation as a physical tool to accelerate the Petasis 3-component reaction without any auxiliary catalyst can significantly shorten the reaction time. The operation is simple. It can be applied to a wide range of substrates. In order to highlight the remarkable utility of the ultrasound in Petasis reaction, we have compared side-by-side the reactivity between the reaction with ultrasound and the one without ultrasound. Results: Using ultrasound, the reaction times of Petasis reactions with various amine substrates including primary and secondary amines, heterocyclic amines, with a wide variety of boronic acids having different substituents (activating and deactivating groups) in the phenyl rings, and with glyoxylic acid and salicylic aldehyde were shortened from 5 to more than 20-fold. Conclusion: We have discovered the first examples of an efficient ultrasound-promoted approach for Petasis reaction to prepare a series of α-arylglycines in high yields and in excellent purities. The low reactivity of the reactions in this study were significantly enhanced by the ultrasound irradiation. By virtue of the acceleration and the operational simplicity, the present ultrasound assisted Petasis reaction can find applications in the synthetic areas of the already widely used Petasis three-component reaction.
Keywords: multi-component